1975
DOI: 10.1002/bjs.1800621202
|View full text |Cite
|
Sign up to set email alerts
|

Surgical complications of implanting pacemakers

Abstract: An analysis of the complications of implanting pacemakers at St George's Hospital between 1967 and 1973 highlights the difficulties of implanting foreign bodies. During this 7 years 1543 pacemakers were implanted in 779 adults. In 91 patients there were 118 implants with surgical complications, most of them due to a pressure necrosis or local infection; 3 septicaemias occurred. The various complications are classified and related to technique of implantation. Methods of management of the complications are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1976
1976
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…In contrast, reviews of cardiac pacemakers [14,15] have reported rates of 0.5 Á/2.5% for wound infections and 4.1% for skin necrosis with pacemaker or wire exposure. A review of 7205 of these implants [15] showed a mean rate of surgical complications of 5.1%. Figures for CIs compare favorably with those reports.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In contrast, reviews of cardiac pacemakers [14,15] have reported rates of 0.5 Á/2.5% for wound infections and 4.1% for skin necrosis with pacemaker or wire exposure. A review of 7205 of these implants [15] showed a mean rate of surgical complications of 5.1%. Figures for CIs compare favorably with those reports.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, hip replacement revision rates have remained rather stable: in 1993 and 1997 revision rates were :/16.8% and 17.3%, respectively [13]. In contrast, reviews of cardiac pacemakers [14,15] have reported rates of 0.5 Á/2.5% for wound infections and 4.1% for skin necrosis with pacemaker or wire exposure. A review of 7205 of these implants [15] showed a mean rate of surgical complications of 5.1%.…”
Section: Discussionmentioning
confidence: 89%
“…Anatomical variations may preclude use of either the cephalic or external jugular veins (Borrie and Lichter, 1975), but the subclavian veins are constantly sited (Keeri-Szanto, 1956). When the cephalic vein is used a puckered scar may result (Siddons and Nowak, 1975) and the superficial position of a catheter in the external jugular vein renders it liable to extrusion (Bluestone et al, 1965;Borrie and Lichter, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Though the cephalic and external jugular veins are not ideally suited as routes of access to the heart for permanent pacing catheters, these veins are commonly used (Siddons and Nowak, 1975;Sowton, 1976). The present study describes the results of using the subclavian vein for permanent cardiac pacing in patients with symptomatic complete atrioventricular block.…”
mentioning
confidence: 97%
“…We felt that the presence of pus and organisms was evidence of generator pocket infection rather than a "foreign body" reaction and accordingly have included them in the analysis. Other authors'6 have reported the frequent presence of sterile effusions found at box change, but there have been fewer reports of purulent fluid indicating prior or active infection in the pouch.20 (4) PENICILLIN HYPERSENSITIVITY Thirteen patients (2 6%) reported penicillin allergy. None received antibiotics.…”
Section: ) Diagnosis Of Infectionmentioning
confidence: 98%